Capitalism expansion and local adaptation: maritime trade network on the North Coast of Java during the early modern period - Sulistiyono, Singgih Tri; Rinardi, Haryono; Yety Rochwulaningsih, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This study shows how the expansion of European capitalism in shipping and maritime trade in Java at the beginning of the modern period did not actually result in a total death of local maritime shipping and trade. What was happening is the process of adaptation of seafarers and local maritime trade. They had to adjust to the new pressing situation following the political and military defeat of the rulers of the port cities on the north coast of Java. This study uses historical perspective by emphasizing on secondary sources to analyze and identify the early modern maritime trade network. Although, it is more like literature review, this study is able to reconstruct the local traders’ adaptation in the middle of capitalism expansion. It is known that seafarers and local maritime traders were unable to keep up with competition in the field of shipping technology so they adapted by filling in business spaces that were occupied by European maritime seamen and traders. In addition, another form of adaptation in dealing with European maritime capitalism is the process of marginalization and contraction in the scale of the shipping network of local seafarers in Java. They finally focused more on doing local shipping rather than international and intra-Asian shipping gradually controlled by European maritime capitalism.